The black hole X-ray binary MAXI J1348–630 in quiescence - Carotenuto, F; Corbel, S; Tzioumis, A (Oxford University Press, 2022)
The properties of the disk/jet coupling in quiescent black hole low mass X-ray binaries (BH LMXBs) are still largely unknown. In this paper we present the first quasi-simultaneous radio and X-ray detection in quiescence of the BH LMXB MAXI J1348–630, which is known to display a hybrid disk/jet connection that depends on the accretion rate. We performed deep X-ray and radio observations using the Chandra X-ray Observatory and the Australia Telescope Compact Array. MAXI J1348–630 is detected for the first time in quiescence at an X-ray luminosity LX = (7.5 ± 2.9) × 1030(D/2.2 kpc)2 erg s−1 : one of the lowest X-ray luminosities observed for a quiescent BH LMXB, possibly implying a short orbital period for the system. MAXI J1348–630 is also detected in radio at LR = (4.3 ± 0.9) × 1026(D/2.2 kpc)2 erg s−1 . These detections allow us to constrain the location of MAXI J1348–630 on the radio/X-ray diagram in quiescence, finding that the source belongs to the standard (radio-loud) track in this phase. This provides a strong confirmation that hybrid-correlation sources follow the standard track at low luminosities and down to quiescence, thus improving our knowledge of the disk/jet connection in BH LMXBs.